Bronchiectases in Children: Overview of Current Clinical Guidelines - A. A. Baranov; L. S. Namazova-Baranova; O. I. Simonova; E. A. Vishneva; L. R. Selimzyanova; E. V. Sereda; N. N. Rozinova; E. N. Tzygina; L. K. Katosova; A. V. Lazareva; Yu. V. Gorinova; O. V. Kustova (Педиатрическая фармакология)
The article is devoted to bronchiectases issue in children and reflects the most actual approaches to the diagnosis and management of patients with this pathology. Information on the true prevalence of bronchiectases both abroad and in Russia varies. Wherein, bronchiectases can be either an independent disease or a manifestation of another pathology, which necessitates an integrated multidisciplinary approach not only for diagnosis but also for patient management with this pathology. The material presented by the authors is based on clinical guidelines developed and approved by the profile association of the Union of Pediatricians of Russia and aimed at raising awareness of specialists providing medical care to children.